2007
DOI: 10.1152/ajpheart.00139.2007
|View full text |Cite
|
Sign up to set email alerts
|

The ligament of Marshall as a parasympathetic conduit

Abstract: The objective of the study was to investigate the morphology, distribution, and electrophysiological profile of the autonomic fibers that innervate the ligament of Marshall (LOM). Gross anatomical dissections were performed in 10 dogs. Sections of the left vagus nerve, left stellate ganglion, and the LOM were immunostained to identify adrenergic and cholinergic nerves. Hearts were also stained for acetylcholinesterase to identify epicardial cholinergic nerves. In vivo electrophysiological studies were performe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
97
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(114 citation statements)
references
References 29 publications
7
97
0
2
Order By: Relevance
“…Although this model of isolated tissue was separated from the central nervous system, acetylcholine release from local ganglia could still facilitate microreentry during AF. Epicardial RFCA to the CS-atrial junction or VOM would modify autonomic ganglia 25 as well as disconnect the macroand microreentrant circuits to terminate AF/AF.…”
Section: Circ Arrhythm Electrophysiolmentioning
confidence: 99%
“…Although this model of isolated tissue was separated from the central nervous system, acetylcholine release from local ganglia could still facilitate microreentry during AF. Epicardial RFCA to the CS-atrial junction or VOM would modify autonomic ganglia 25 as well as disconnect the macroand microreentrant circuits to terminate AF/AF.…”
Section: Circ Arrhythm Electrophysiolmentioning
confidence: 99%
“…37,38 When the early tachyarrhythmias beats originated from (1) the posterolateral LA wall next to the left PVs or (2) Bachmann bundle insertion into the superior RA wall, repolarization changes were concentrated in the atrial regions in which the tachyarrhythmia sites of origin were identified. The tachyarrhythmia sites of origin identified in the posterolateral LA wall (most frequently associated with left dorsal mediastinal nerve stimulation) were adjacent to the ligament of Marshall (which includes predominantly cholinergic neural elements in the canine heart 39 as well as to the LA and dorsal atrial ganglionated plexuses. Likewise, the tachyarrhythmia sites of origin identified in Bachmann bundle insertion into the superior RA (all associated with right dorsal mediastinal nerve stimulation) lay next to the superior extension of the RA ganglionated plexus.…”
Section: Relation To Neural Influences On the Atriamentioning
confidence: 99%
“…[20][21][22] The structural and functional characteristics of these regions, including the narrow and thick musculature, complex myofibril arrangement, and proximity to the autonomic ganglia and the ligament of Marshall may support the formation of a slow conduction obstacle of reentry due to the nontransmurality of the AF ablation lesions. 23,24) Study limitations : We did not use a 3D electroanatomical mapping system to evaluate the circuit of the induced ATs, or to confirm the block line along LARL. Therefore, there were some limitations in this study regarding assessment of the course of induced ATs.…”
Section: Discussionmentioning
confidence: 99%